ANALISIS ISLAMIC BRANDING DAN DIGITAL MARKETING TERHADAP MINAT PEMBELIAN PRODUK AYAM PENYET SURABAYA CABANG CILACAP - Nur Triwibowo, Rony; Yusuf, Dede; Irawansah, Opi; Cahyani, Venna; Naim, Sinta (JURNAL EKONOMI, 2024)
The restaurant industry is becoming more and more competitive, so entrepreneurs must develop relevant and innovative marketing plans that may be used as weapons in the marketplace. Islamic branding, which involves using an Islamic identity (including Islamic writing, Sharia, Islamic names, and halal labels) in product marketing, is one tactic that can be used. Digital marketing and Islamic branding are two marketing techniques used to sway consumers' interest in making purchases. The purpose of this study is to examine how interest in buying items from the Cilacap branch of Ayam Penyet Surabaya is influenced by Islamic branding and digital marketing.